A Framework for a Trans-disciplinary, Translational Research Group for Building Innovation. (2015) - Donofrio, Mark
Abstract: This paper outlines a framework for the formation of a research group aimed at promoting innovation in the building industry. The built environment in the United States is failing; economic, social, environmental and technological performance of buildings as well as the industry responsible for their creation has not kept pace with other industries essential to a ensuring a healthy society. While it would appear that research activity is prevalent in academia and, to some extent, in professional practice, the building industry is slow to change. The building industry is examined to identify the barriers currently in place that limit innovation. This paper proposes the formation of a trans-disciplinary group of academics and industry partners focused on translational research aimed at promoting much needed innovation in the building industry. The complexity of the problems needing to be addressed by the building industry is often beyond the scope of knowledge of any one particular field. This framework proposes to move beyond interdisciplinary research, where knowledge is transferred between collaborators, and rather strives for a trans-disciplinary model where team members transcend their own disciplines to inform one another's work. In addition, the research carried out by this group is intended to be translational. Modelled after the successful approach currently implemented in the medical profession, translational research results in a feedback loop where basic research is tested in application. Results become inputs to a new round of basic research, which are then tested again. This cycle continues with new research questions continuously being influenced by the limitations of previous questions. By more directly connecting the efforts of research in academia with the application in practice, the potential exists to make research more visible to both those with the power to implement it, practitioners and industry, and those able to benefit from it, end users.